Deciphering Degassing and Source Effects in Cl Isotopes in Melt Inclusions: The Possible Role of Amphibole in the Magma Source of Stromboli (Aeolian Island Arc) - Bouvier, Anne-Sophie; Rose-Koga, Estelle F.; Chapuis, Alexis (Frontiers in Earth Science, 2022)
Chlorine isotopes have emerged as a new geochemical tool over the past 15 years. Most of the data consist of bulk rock data, with a minority carried out in situ on melt inclusions using secondary ion mass spectrometry. More data are necessary to understand the relationship between δ37Cl measured in melt inclusions and that in bulk rocks from the same volcanic center. Here we have analyzed a suite of melt inclusions entrapped in olivine Fo63-85, as well as some from clinopyroxene crystals, from a single hand-sample from the Vancori unit of Stromboli, Aeolian Islands. The 27 selected melt inclusions have major element compositions ranging from high potassium alkali basalt to evolved shoshonite. Their δ37Cl vary from −2.6 ± 0.1‰ to +1.2 ± 0.2‰, a far larger range than for Stromboli bulk rocks. In this dataset, the δ37Cl variation in melt inclusions is not related to Cl degassing, or to fractional crystallization. Instead, correlations between δ37Cl and S/Cl, K2O and trace element ratios suggest mixing of two Cl endmembers with distinct δ37Cl signatures. A first endmember is characterized by high potassium alkali basalt compositions, high Ba/La (∼28), high S/Cl, and high δ37Cl (>1‰), confirming the influence in the mantle source of an aqueous fluid and providing a new constraint on its composition: that it derives from the breakdown of amphibole. The second endmember has a more evolved composition, high La/Yb, low S/Cl, and low δ37Cl (<−2‰), identifying the influence of a solute-rich component derived from subducted sediments. The δ37Cl data thus help refine the two sources initially identified from bulk rock studies and δ37Cl proves to be a potential tracer for amphibole.